Roots and Routes: Krio Identity in Postcolonial London - Ashcroft, Shaka (Black theology, 2015)
The question of identity is important to all humans. This is true of the Krios from The Gambia. The Krios are an ethnic group that consists of liberated formerly enslaved people. Most of these Krios came to The Gambia from Sierra Leone and Liberia from around 1831 to 1833 during the governorship of Sir Charles McCarthy. They came as labour to help Colonial Gambia develop her economy and to supplement The Gambia militia in times of need, while others came to increase their knowledge at colleges and universities. When the Krios came to The Gambia they settled in Banjul and McCarthy Island. Divisions in the communities gave rise to a new set of identities, which were different from the various countries from which they had been liberated. However, today there are claims that apart from the fact that they have developed new identities, the Krios have also maintained some of their indigenous traditions. The salient question, therefore, is the extent to which the Krios in The Gambia have developed new identities while maintaining some of their old traditions and how they were able to achieve this. This paper arises as a result of the interactions with some of the Krio youth in The Gambia, who wanted to know about the Krio culture and how they could maintain their identity as Krios even when they go abroad for further studies.